Franchised States and the Bureaucracy of Peace - Schia, Niels Nagelhus (Rethinking Peace and Conflict Studies, 2018)
This book examines a new type of state formation evoked by the rise of transnational rule, what Schia calls franchised states. Drawing on anthropological studying-through fieldwork within the UN organization, he demonstrates how peacebuilding activities turned Liberia into an object of governing, whereby the UN, in seeking to build the state, also became the state. The sovereign state of Liberia here emerges as a franchise rather than a self-contained entity. Two implications follow: First, that international peacebuilding turns post-conflict countries into clients of the international community. Second, that "sovereignty" is no longer exclusively associated with the state: it is organized in and through specific practices of governing where a state actor is only one among a range of actors. With these findings, the book moves beyond previous work on peacebuilding by focusing on the unbundling of sovereignty. It contributes to the literature on the changing forms of sovereignty by showing the specific ways in which sovereignty is organized, packaged and enacted, often by actors working under international auspices. This book will be of interest to practitioners and students interested in international organizations, international relations, the study of international practices, UN, and peacebuilding.